1993
DOI: 10.1007/bf01642799
|View full text |Cite
|
Sign up to set email alerts
|

The time-dependent expression of keratins 5 and 13 during the reepithelialization of human skin wounds

Abstract: Summary. The time-dependent reepithelialization of 55 human surgical skin wounds with a wound age between 8h and more than 2 months was investigated by the immunohistochemical localization of cytokeratins 5 and 13. A complete, rebuilt epidermal layer over the wound area was first detectable in a 5-day-old wound, while all wounds of more than 18 days duration contained a completely reepithelialized wound area. Between 5 and 18 days the basal layer of keratinocytes showed -in contrast to normal skin -only some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…In our series, an enhanced expression of Ki 67 antigen in keratinocytes covering the previous epithelial lesion could not be established. This supports the hypothesis that keratinocyte migration which starts from areas of undamaged skin with an increased proliferation activity but not local proliferation plays the major role in reepithelialization [2,17]. In the epidermal layers adjacent to the wound area, however, an increased number of Ki 67 positive basal cells occurred in the most cases and a wave-like course in the numbers of proliferating basal cells with advancing distance from the wound margins could be observed according to experimental results.…”
Section: Discussionsupporting
confidence: 86%
“…In our series, an enhanced expression of Ki 67 antigen in keratinocytes covering the previous epithelial lesion could not be established. This supports the hypothesis that keratinocyte migration which starts from areas of undamaged skin with an increased proliferation activity but not local proliferation plays the major role in reepithelialization [2,17]. In the epidermal layers adjacent to the wound area, however, an increased number of Ki 67 positive basal cells occurred in the most cases and a wave-like course in the numbers of proliferating basal cells with advancing distance from the wound margins could be observed according to experimental results.…”
Section: Discussionsupporting
confidence: 86%
“…This correlated to a nearly 13-fold reduction in slope for the K10 H-score across the epithelial tongue (Fig 5, third row). Defects in reepithelialization are associated with chronic wounds and malignant transformation in which reciprocal expression of K10 and K13 are often observed [29, 30]. Again, we observed that Gα 11 KO/Gα q -WT control animals had a steady, nearly linear increase in K13 H-score across the epithelial tongue that was abrogated in the Gα 11 KO/Gα q -eKO animals.…”
Section: Resultssupporting
confidence: 52%
“…The change of CK expression, therefore, in the epidermis of fairly remote areas from wound edges does not seem to be caused by a hyperproliferative state of keratinocytes. Betz et al (1993) have reported that the basal cell layer of the new epithelium first showed a complete positive staining for CK 5 after approximately 13 days survival time. The present study, however, revealed that positive staining for CK 5 was noted in the basal cell layer of the epidermal tongue 1 day after wounding, although the staining intensity was decreased.…”
Section: Discussionmentioning
confidence: 97%